Emerging perspectives on values in organizations - Gilliland, Stephen; Steiner, Dirk; Skarlicki, Daniel (Research in social issues in management., 2003)
The chapters in this volume offer new and innovative ways to view values related to fairness, as well as work-related values, their antecedents and consequences. All have been peer reviewed prior to their publication. This volume consists of two parts. The first part focuses on value-based theories in organizations. The papers in this section address issues such as how to define, classify and study values; how values influence fairness by influencing what people believe what they deserve; how one's own identity relates to fairness perceptions, and how values and norms affect the way that people perceive or construe events.